Identifikasi dan Analisis Isu-Isu Kritis dalam Historiografi Indonesia Kontemporer: Studi Empiris terhadap Perspektif Akademisi Sejarah - Rahmania Arunita Hendarto; Etmi Hardi (Lembaga Yasin AlSys, 2026)
Although contemporary Indonesian historiography has received attention in various studies, empirical research that specifically identifies and analyzes critical issues based on the perspectives of history academics remains relatively limited. This study aims to identify and analyze various strategic issues that influence the development of contemporary Indonesian historiography through the views of history academics. This study uses a qualitative approach with a multiple case study design, involving 20 history academics selected through purposive sampling and developed through snowball sampling. Data were collected through semi-structured interviews and document analysis, and were then analyzed using reflexive thematic analysis. The results show that six main issues dominate contemporary Indonesian historiography, namely objectivity and bias in historical interpretation, the dominance of state narratives, the low representation of marginal groups, the need for historiographical decolonization, the impact of digitalization on historical research practices, and the urgency of renewing historiographical methodology. The findings also show that academics view historiography as a construction of knowledge influenced by power relations, social context, and technological development, thereby requiring a more inclusive, critical, and interdisciplinary approach. The conclusion of this study affirms that the development of contemporary Indonesian historiography needs to be directed toward renewing paradigms, methods, and historical sources that are more critical and responsive to social and digital change. This study contributes theoretically to strengthening critical historiography and postmodern historiography perspectives in the Indonesian context, and contributes methodologically through the application of a multiple case study design and reflexive thematic analysis in historiographical studies. The practical implications of this study include the development of history curricula, archival management policies, and innovations in historical research methodology, while also opening opportunities for further studies on the use of digital humanities and artificial intelligence in the development of Indonesian historiography.